Spanish Pediatric Inflammatory Bowel Disease Diagnostic Delay Registry: SPIDER Study From Sociedad Española de Gastroenterología, Hepatología y Nutrición Pediátrica - Santiago Jiménez Treviño; Gemma Pujol Muncunill; Rafael Martín-Masot; Alejandro Rodríguez Martínez; Oscar Segarra Cantón; Luis Peña Quintana; Honorio Armas Ramos; Francisco Javier Eizaguirre Arocena; Josefa Barrio Torres; José Ignacio García Burriel; Luis Ortigosa Castillo; Ester Donat Aliaga; et al. (Frontiers Media S.A., 2020)
Background and Aims: Diagnostic delay (DD) is especially relevant in children with inflammatory bowel disease, leading to potential complications. We examined the intervals and factors for DD in the pediatric population of Spain.Methods: We conducted a multicentric prospective study, including 149 pediatric inflammatory bowel disease patients, obtaining clinical, anthropometric, and biochemical data. Time to diagnosis (TD) was divided into several intervals to identify those where the DD was longer and find the variables that prolonged those intervals. Missed opportunities for diagnosis (MODs) were also identified.Results: Overall TD was 4.4 months (interquartile range [IQR] 2.6-10.4), being significantly higher in Crohn's disease (CD) than in ulcerative colitis (UC) (6.3 [IQR 3.3-12.3] vs. 3 [IQR 1.6-5.6] months, p = 0.0001). Time from the visit to the first physician until referral to a pediatric gastroenterologist was the main contributor to TD (2.4 months [IQR 1.03-7.17] in CD vs. 0.83 months [IQR 0.30-2.50] in UC, p = 0.0001). One hundred and ten patients (78.3%) visited more than one physician (29.9% to 4 or more), and 16.3% visited the same physician more than six times before being assessed by the pediatric gastroenterologist. The number of MODs was significantly higher in CD than that in UC patients: 4 MODs (IQR 2-7) vs. 2 MODs ([IQR 1-5], p = 0.003). Referral by pediatricians from hospital care allowed earlier IBD diagnosis (odds ratio 3.2 [95% confidence interval 1.1-8.9], p = 0.025).Conclusions: TD and DD were significantly higher in CD than those in UC. IBD patients (especially those with CD) undergo a large number of medical visits until the final diagnosis.